Estimate Bayes Robust of a parameter(β) for the second maximum likelihood of the standard Frechet distribution With: An applied study of Corona patients in Karbala Governorate - Wahab Neaama Naser Allah, Mahdi; Ali Ghany, Tamara (Iraqi Journal for Administrative Sciences, 2024)
The study deals with the estimation of the parameter (B) of the Frechet distribution by using the hippocampal bay method depending on the pollutant class for the second greatest place (ML.II.ε) at two types of the standard base distribution and the contaminant base distribution, which is when the distribution is the standard basis and the contaminated distribution. The Kama distribution and when the standard baseline distribution and the contaminated base distribution is the Lindley distribution when a quadratic loss is indicative. The primary contaminant distribution is Lindley, and emphasizes that it should be used to estimate the parameters of the standard base distribution, the Freight distribution, compared to the pollutant gamma distribution.